Wiskott-Aldrich syndrome mutation in two Turkish siblings with X-linked thrombocytopenia - Göksel Leblebisatan; Ali Bay; Noriko Mitsuiki; Osamu Ohara; Kenichi Honma; Kohsuke İmai; Shigeaki Nonoyama (Turkish Journal of Hematology, 2011)
Wiskott-Aldrich syndrome (WAS) is a clinical condition characterized by thrombocytopenia, eczema, and life-threatening infections. In some cases autoimmunity-related problems and even malignancy might be seen; however, some patients have milder clinical manifestations due to mutations in the same gene family, such as in X-linked thrombocytopenia (XLT), which is generally not associated with serious symptoms of disease, except for thrombocytopenia. Herein we report 2 siblings with chronic thrombocytopenia that were diagnosed with XLT based on a missense mutation in the WASP gene (223G>A, Val75Met). To the best of our knowledge this mutation has not been previously reported in a Turkish patient with XLT.